Building technology platform aimed to develop service robot with embedded personality and enhanced communication with social environment - Aleksandar Rodić; Miloš Jovanović; Ilija Stevanović; Branko Karan; Veljko Potkonjak (Digital Communications and Networks, 2015)
The paper is addressed to prototyping of technology platform aimed to develop of ambient-aware human-centric indoor service robot with attributes of emotional intelligence to enhance interaction with social environment. The robot consists of a wheel-based mobile platform with spinal (segmented) torso, bi-manual manipulation system with multi-finger robot hands and robot head. Robot prototype was designed to see, hear, speak and use its multimodal interface for enhanced communication with humans. Robot is capable of demonstrating its affective and social behavior by using audio and video interface as well as body gestures. Robot is equipped with advanced perceptive system based on heterogeneous sensorial system, including laser range finder, ultrasonic distance sensors and proximity detectors, 3-axis inertial sensor (accelerometer and gyroscope), stereo vision system, 2 wide-range microphones, and 2 loudspeakers. The device is foreseen to operate autonomously but it may be also operated remotely from a host computer through wireless communication link as well as by use of a smart-phone based on advanced client-server architecture. Robot prototype has embedded attributes of artificial intelligence and utilizes advanced cognitive capabilities such as spatial reasoning, obstacle and collision avoidance, simultaneous localization and mapping, etc. Robot is designed in a manner to enable uploading of new or changing existing algorithms of emotional intelligence that should provide to robot human-like affective and social behavior. The key objective of the project presented in the paper regards to building advanced technology platform for research and development of personal robots aimed to use for different purpose, e.g. robot-entertainer, battler, robot for medical care, security robot, etc. In a word, the designed technology platform is expected to help in development human-centered service robots to be used at home, in the office, public institutions, etc.